Japan's multinational enterprises - Yoshino, M. Y. (Cambridge : Harvard University Press, 1976)
This is a detailed study of the evolution of Japanese multinational enterprises in the 1970's and before. The book provides a summary of the development of the Japanese oil industry, its relationship with the major international oil companies, and its evolving strategy, responding in part to evolving Japanese government policy
Includes bibliographical references and index.
lje 24/04/2018
Loans
Keywords: Corporations, Japanese; International business enterprises